Stagnation-point flow of Casson fluid in Darcy-Forchheimer porous media with newtonian heating effect - Ahmad, Kartini; Hanouf, Zahir (Medwell Journals, 2019)
Flow of Casson fluid in Darcy-Forchheimer porous medium near a stagnation point over a stretching sheet with Newtonian heating effect is investigated in this paper. The boundary-layer equations are solved numerically for f"(0) and θ(0) using the Keller-box method for some values of Casson fluid parameter (β), porous media parameter (κ1), inertia-coefficient parameter (κ2), Newtonian heating parameter (γ), Prandtl number (Pr) and stretching parameter (c).